2021
DOI: 10.1161/atvbaha.120.316389
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia Impairs Clearance of Neutrophil Extracellular Traps and Promotes Inflammation and Atherosclerotic Plaque Progression

Abstract: Objective: Hypercholesterolemia-induced NETosis and accumulation of neutrophil extracellular traps (NETs) in the atherosclerotic lesion exacerbates inflammation and is causally implicated in plaque progression. We investigated whether hypercholesterolemia additionally impairs the clearance of NETs mediated by endonucleases such as DNase1 and DNase1L3 and its implication in advanced atherosclerotic plaque progression. Approach and Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 47 publications
2
24
0
3
Order By: Relevance
“…One of the earlier studies showed that the regulatory T cells (Tregs) activate anti-in ammatory macrophages, suppress the formation of foam cells, and affect cholesterol metabolism, all of which have an atherosclerosis-preventing effect [9]. In contrast, macrophages, and neutrophil extracellular traps (NETs) were shown to promote in ammation and atherosclerotic plaque progression [10,11]. Although prior research has shown that different immune cells and immune system-related pathways were involved in the progression of carotid atherosclerotic plaques, none of the reports have determined the major molecular processes and how they interact with the in ammation-linked pathways to control the progression of the carotid atherosclerotic plaques.…”
Section: Introductionmentioning
confidence: 99%
“…One of the earlier studies showed that the regulatory T cells (Tregs) activate anti-in ammatory macrophages, suppress the formation of foam cells, and affect cholesterol metabolism, all of which have an atherosclerosis-preventing effect [9]. In contrast, macrophages, and neutrophil extracellular traps (NETs) were shown to promote in ammation and atherosclerotic plaque progression [10,11]. Although prior research has shown that different immune cells and immune system-related pathways were involved in the progression of carotid atherosclerotic plaques, none of the reports have determined the major molecular processes and how they interact with the in ammation-linked pathways to control the progression of the carotid atherosclerotic plaques.…”
Section: Introductionmentioning
confidence: 99%
“…However, acute elevation of extracellular DNA, such as that happens during an acute inflammatory response, requires rapid systemic elevation of DNase activity to restore homeostasis and prevent the onset of an inflammatory response. 10 Interestingly, several autoimmune diseases are associated with decreased systemic DNase activity, increased extracellular DNA levels, and increased anti‐ds‐DNA autoantibodies. 10 , 11 , 12 , 13 , 14 For example, the decreased DNase activity in systemic lupus erythematosus (SLE) is associated with either single nucleotide polymorphisms (SNPs) or mutations in DNase1/DNase1L3 15 , 16 , 17 , 18 , 19 , 20 or the presence of neutralizing antibodies which block the activity of DNase1/DNase1L3.…”
Section: Introductionmentioning
confidence: 99%
“…A depuração das NETs é mediada por desoxirribonucleases (DNases), que degradam o arcabouço de DNA das NETs e facilitam a sua fagocitose por macrófagos (18,19).…”
Section: Costa Victor Ferreiraunclassified
“…A TREX1 é uma DNase intracelular, que fica ancorada na membrana nuclear, e, portanto, dependeria da entrada das NETs nas células para degradação (23). A DNase 1 é secretada e tem sua expressão principalmente no pâncreas e por glândulas salivares (19,20,22), podendo também ser expressa no trato gastrointestinal e nos rins (24). Essa é a principal DNase presente no soro de humanos e de camundongos, é juntamente com a DNase γ, é responsável pela maior parte da atividade DNase detectada nesse tipo de amostra (24).…”
Section: Costa Victor Ferreiraunclassified
See 1 more Smart Citation